Respuesta :
I got that x=-5.37003947. I am not sure that I put everything under the square root that needed to be there so I hope this helps.
Answer:
[tex]x=-5.37[/tex]
Step-by-step explanation:
The equation is:
[tex]2^5\cdot{\sqrt{(x+6)^3}}+3=19[/tex]
We can simplify by taking over 3 to the left hand side and divide the equation by 2^5 and then squaring both sides to get rid if the square root:
[tex]2^5\cdot{\sqrt{(x+6)^3}}=19-3[/tex]
[tex]\sqrt{(x+6)^3}=16/2^5[/tex]
[tex](x+6)^3=(0.5)^2[/tex]
[tex](x+6)^3=0.25[/tex]
We can take the third root on both sides:
[tex](x+6)=0.63[/tex]
[tex]x=0.63-6=-5.37[/tex]